Outbreak of listeriosis associated with consumption of deli meats in a hospital, Germany, February to March 2023 - Feige, Lena; Walter, Nicole; Fawzy Mohammed, Ahmad Mahmoud; Schultze, Tilman; Hassel, Melanie; Vogt, Manfred; Zanger, Philipp; Schoeps, Anja (Eurosurveillance, 2025)
Listeria monocytogenes can cause severe illness in individuals with weakened immune systems. In March 2023, L. monocytogenes was isolated from blood (n = 2) or pleural fluid (n = 1) of three febrile patients receiving synthetic glucocorticoids in a tertiary hospital in Germany. Food supply records suggested sliced parboiled sausage as the likely source, and L. monocytogenes was isolated from four samples of sealed packaged sliced sausages and ham from one manufacturer. The patient and food isolates clustered within 0-4 allelic differences. Counts of L. monocytogenes in all four food samples were < 100 colony-forming units (CFU)/g, a threshold in the European Union legislation for ready-to-eat products with specific conditions. Our findings, aligned with previous evidence, highlight that persons with weakened immune systems should not be exposed to L. monocytogenes in food. We advocate for a clear communication of deli meats as high-risk foods, so individuals with weakened immune systems can adjust their diet to reduce their risk for invasive listeriosis. We recommend an update of dietary and hygiene guidelines for care settings and private homes where food is prepared, handled and stored for persons with weakened immune systems.
Online veröffentlicht: 20. Februar 2025
Gesehen am 30.09.2025